Framework for financial hardship indebtedness management in abandoned housing projects in Malaysia - Saʿid Adekunle Mikail; Noor Suhaida Kasri; Saba' Radwan Jamal Elatrash; Abideen A. Adewale (ISRA International Journal of Islamic Finance, 2018)
Purpose: This paper aims to examine the existing practices and pertinent issues affecting Islamic banks and their customers in abandoned housing projects (AHPs) to ensure compliance with Sharīʿah and statutory requirements. Design/methodology/approach This study employs the qualitative research method using the inductive approach to analyze both primary and secondary data and sources. Data collection involved a series of semi-structured interviews with five volunteering Islamic banks and a representative of Abandoned Property Owners Association Malaysia (Victims). Statutory acts, regulatory policies, guidelines, directives and standards were also analyzed. Findings The result indicates developer's default, underlying contracts, regulatory arbitrage and bureaucracy, attitudinal disposition of customers and sell-then-build approach as major factors of AHP's conundrum. Practical implications This study has suggested both short- and long-term solutions based on the principles of justice, public interests and removal of hardship to resolve and effectively manage financial hardship indebtedness arising from housing abandonment. Further, part of the proposed solutions would also reshape housing development policies and home financing transactions. Originality/value The quest for this research demonstrated Islamic banking industry's initiatives to find lasting solutions to perennial issues of AHPs.
Keywords: 330; Abandoned housing projects; Financial hardship; Home buyers; Housing developer; Indebtedness management; Islamic home financing